2007
DOI: 10.12968/bjcn.2007.12.sup1.23048
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing with clients with chronic leg ulceration

Abstract: On order to meet the holistic needs of the client with chronic illness, the nurse is required to adopt many different approaches to care. This article will explore one client-centred counselling approach that can be used by community practitioners to address behavioural change and improve concordance. The techniques are illustrated with an example of where motivational interviewing has been used to great success--in the 'Look After Your Legs' (LAYL) programme undertaken by West Gloucestershire primary care tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…healthcare professionals have a key role in enabling patients to feel in control of their condition. Morris and white (2007) suggested that communication between the nurse and patient as part of a therapeutic relationship promotes a sense of control and self-efficacy.…”
Section: Psychological Effectsmentioning
confidence: 99%
“…healthcare professionals have a key role in enabling patients to feel in control of their condition. Morris and white (2007) suggested that communication between the nurse and patient as part of a therapeutic relationship promotes a sense of control and self-efficacy.…”
Section: Psychological Effectsmentioning
confidence: 99%
“…34 Although few studies explicate the exact mechanisms related to the behavioral intervention on study outcomes, these data provide some evidence to support the use of ME in clinical populations such as those with leg ulcers. 34 Although few studies explicate the exact mechanisms related to the behavioral intervention on study outcomes, these data provide some evidence to support the use of ME in clinical populations such as those with leg ulcers.…”
Section: Discussionmentioning
confidence: 94%
“…The introduction of chronic medication into a patient's life often means that new behavioral patterns need to be established but if the message is not clear, for any factors, accurately understood by the patient; the patients' well-being is further compromised. [24] Therefore, adherence to treatment becomes exceptionally important for these patients who have been diagnosed with rheumatic disorders.…”
Section: Discussionmentioning
confidence: 99%